Pengaruh Regulasi Emosi Terhadap Self-Control Siswa Kelas X Akuntansi Keuangan Lemabaga di SMKN 1 Bogor - Intan Amalia Putri; Rusdi Kasman; Noneng Siti Rosidah (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Adolescence requires students to have good self-control skills in managing behavior and emotions. One factor suspected of influencing self-control is emotional regulation. This study aims to determine the level of emotional regulation, self-control level, and the effect of emotional regulation on self-control of class X students of Financial Accounting Institutions at SMKN 1 Bogor. This study uses a quantitative approach with an explanatory method and a simple causal design. Data analysis was carried out using simple linear regression. The results showed that students' emotional regulation was in the moderate category at 74.8%, while self-control was in the high category at 45.6%. The results of the regression test showed a regression coefficient of 0.774 with a significance value of 0.000. The R Square value of 0.174 indicates that emotional regulation contributed 17.4% to students' self-control. These findings indicate that emotional regulation has a positive and significant effect on students' self-control, so improving emotional regulation skills is important to support students' self-control in the educational context.